Parasites of Arctic char (Salvelinus alpinus) in North America: a systematic literature review and an analysis of contemporary data from anadromous populations from Nunavut - Les N. Harris; Phillip R. Morrison; Michael W. Johnson; Sara Bolduc; Ariane Côté; Amélie Papillon; Justine Lapointe; Xuehan Qu; David J. Yurkowski; Connor W. Faulkner; Colin P. Gallagher; Lauren N. Wiens; et al. (Reviews in Fish Biology and Fisheries, 2026)
Parasites play a critical yet understudied role in Arctic ecosystems, particularly within key subsistence species such as Arctic char ( Salvelinus alpinus ). As the Arctic undergoes rapid climate-driven change, establishing baseline parasite biodiversity is essential for monitoring ecological shifts and anticipating emerging health and conservation concerns. This study provides the most comprehensive assessment to date of Arctic char parasites in the North American Arctic by integrating a systematic literature review with new empirical data from 378 Arctic char collected across five Nunavut areas (2020–2024). The literature review (30 studies, 1956–2024) documented 67 parasite taxa—48 identified to species—with helminths (nematodes, cestodes, trematodes, acanthocephalans) dominant. Overall, 82% of taxa occurred in anadromous Arctic char and 54% in freshwater forms, including 22 species unique to anadromous fish. Our empirical assessment identified 35 parasite taxa—23 to species level—including several previously unreported from Arctic char in this region. Common and widespread parasites documented in the empirical assessment included Brachyphallus crenatus , Derogenes varicus , Bothrimonus sturionis , and Alloopistholecithum gibbosum , although notable spatial variation occurred in community composition and infection intensity. The occurrence of rare and previously unreported parasites may suggest emerging shifts in host–parasite dynamics potentially linked to changing prey availability and northward species range expansions. Together, these findings establish an essential baseline for Arctic char parasite biodiversity and highlight the need for continued monitoring to track future changes driven by climate warming, shifting food webs, and their implications for fish health and food security in northern Indigenous communities.

Integrating climate adaptation and peacebuilding: capacity development in climate and conflict-affected communities - Luisa Fernanda Bedoya Taborda; Tiffany H. Morrison; Michele L. Barnes (Global Environmental Change, 2026)

Expert consensus on passive heating interventions to promote skeletal muscle strength and mass: a delphi study - Elisa Lemos; Ian B. Stewart; Patrick Rodrigues; Shawnda A. Morrison; Lee Wharton; Christopher J. Tyler; Stephen S. Cheung; Sebastian Racinais; Ralph J. F. H. Gordon; Alex Lloyd; Julien D. Périard; Katsumasa Goto; et al. (European Journal of Applied Physiology, 2026)
Purpose Passive heating has emerged as a potential non‑exercise method to support muscle strength and mass, but its application is limited by inconsistent protocols and unclear dosage and safety guidelines. This study used a Delphi methodology to establish expert consensus on key parameters for passive heating interventions targeting neuromuscular and muscle morphology outcomes. Methods An international panel of academic experts (≥ 3 peer‑reviewed publications in passive heating and neuromuscular function) completed a two‑round Delphi process. Round 1 gathered open‑ended responses on passive heating strategies, intervention targets, and safety. In Round 2, experts ranked the importance of generated statements. Consensus was defined as ≥ 70% ranking a statement as either first or second in importance. Results Eleven experts completed Round 1 and ten in Round 2. From 177 qualitative responses, 130 statements were evaluated, with 11 reaching consensus (80–100% agreement; interquartile range = 0–1). Hot‑water immersion was prioritised as the most optimal passive heating modality. Experts agreed on targeting muscle temperatures of 39–40 °C, ~ 60-minute session durations, and once‑daily exposure as key intervention parameters. Strong consensus was also reached for monitoring core temperature and cardiovascular strain (e.g., heart rate, blood pressure) to ensure participant safety. No consensus was reached on a single target population or the total intervention duration. Conclusion This Delphi study provides a consensus‑based framework outlining key parameters and safety considerations for passive heating interventions. These findings do not establish efficacy but identify priority variables to inform future experimental research and cautious translation into applied and clinical contexts.

Distinguishing natural from mining-related metal sources by including streambank groundwater data in a stream mass loading study - Andrew H. Manning; Robert L. Runkel; Jean M. Morrison; Sara Warix; Richard B. Wanty; Katherine Walton-Day; Michael Snook (Journal of Contaminant Hydrology, 2026)

Global review of jellyfish monitoring programs to design fit-for-purpose approaches - Clare Morrison; Alienor L.M. Chauvenet; Michael J. Kingsford; Iain M. Suthers; Ana Rubio; Cathy H. Lucas; Kylie Pitt (Marine Environmental Research, 2026)

Clarifying the role of the resist–accept–direct framework in supporting resource management planning processes - Gregor W. Schuurman; Wylie Carr; Cat Hawkins Hoffman; David J. Lawrence; Brian W. Miller; Erik A. Beever; Jean Brennan; Katherine R. Clifford; Scott Covington; Shelley D. Crausbay; Amanda E. Cravens; John Gross; et al. (Conservation Biology, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Biometeorological feedbacks on peatlands: Raising the water table to reduce meteorologically-related stress on cattle - Wanda Gherca; Inke Forbrich; Adrien Jacotot; Sara H. Knox; Paul G. Leahy; Ross Morrison; Torsten Sachs; Elke Eichelmann (Agricultural and Forest Meteorology, 2025)

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Overcoming lock-in of science-policy responses to reef heating - Tiffany H. Morrison; Jon Barnett; Georgina G. Gurney; Jacqueline Lau; Michele L. Barnes; Josh Cinner; Missaka Hettiarachchi; Pip Cohen (Marine Policy, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Agreements for conserving migratory shorebirds in the Asia–Pacific are better fit for addressing habitat loss than hunting - Eduardo Gallo-Cajiao; Tiffany H. Morrison; Richard A. Fuller (Ambio, 2024)

Floating debris and organisms can raft to Antarctic coasts from all major Southern Hemisphere landmasses - Hannah R. S. Dawson; Matthew H. England; Adele K. Morrison; Veronica Tamsitt; Ceridwen I. Fraser (Global Change Biology, 2024)
Antarctica's unique marine ecosystems are threatened by the arrival of non‐native marine species on rafting ocean objects. The harsh environmental conditions in Antarctica prevent the establishment of many such species, but warming around the continent and the opening up of ice‐free regions may already be reducing these barriers. Although recent genomic work has revealed that rafts—potentially carrying diverse coastal passengers—reach Antarctica from sub‐Antarctic islands, Antarctica's vulnerability to incursions from Southern Hemisphere continents remains unknown. Here we use 0.1° global ocean model simulations to explore whether drift connections exist between more northern, temperate landmasses and the Antarctic coastline. We show that passively floating objects can drift to Antarctica not only from sub‐Antarctic islands, but also from continental locations north of the Subtropical Front including Australia, South Africa, South America and Zealandia. We find that the Antarctic Peninsula is the region at highest risk for non‐native species introductions arriving by natural oceanic dispersal, highlighting the vulnerability of this region, which is also at risk from introductions via ship traffic and rapid warming. The widespread connections with sub‐Antarctic and temperate landmasses, combined with an increasing abundance of marine anthropogenic rafting vectors, poses a growing risk to Antarctic marine ecosystems, especially as environmental conditions around Antarctica are projected to become more suitable for non‐native species in the future.

Governance of advanced materials: Shaping a safe and sustainable future - Monique Groenewold; Eric A.J. Bleeker; Cornelle W. Noorlander; Adriënne J.A.M. Sips; Margriet van der Zee; Robert J. Aitken; James H. Baker; Martine I. Bakker; Evert A. Bouman; Shareen H. Doak; Damjana Drobne; Verónica I. Dumit; et al. (NanoImpact, 2024)

A circumpolar study unveils a positive non‐linear effect of temperature on arctic arthropod availability that may reduce the risk of warming‐induced trophic mismatch for breeding shorebirds - Aurélie Chagnon‐Lafortune; Éliane Duchesne; Pierre Legagneux; Laura McKinnon; Jeroen Reneerkens; Nicolas Casajus; Kenneth F. Abraham; Élise Bolduc; Glen S. Brown; Stephen C. Brown; H. River Gates; Olivier Gilg; et al. (Global Change Biology, 2024)
Seasonally abundant arthropods are a crucial food source for many migratory birds that breed in the Arctic. In cold environments, the growth and emergence of arthropods are particularly tied to temperature. Thus, the phenology of arthropods is anticipated to undergo a rapid change in response to a warming climate, potentially leading to a trophic mismatch between migratory insectivorous birds and their prey. Using data from 19 sites spanning a wide temperature gradient from the Subarctic to the High Arctic, we investigated the effects of temperature on the phenology and biomass of arthropods available to shorebirds during their short breeding season at high latitudes. We hypothesized that prolonged exposure to warmer summer temperatures would generate earlier peaks in arthropod biomass, as well as higher peak and seasonal biomass. Across the temperature gradient encompassed by our study sites (>10°C in average summer temperatures), we found a 3‐day shift in average peak date for every increment of 80 cumulative thawing degree‐days. Interestingly, we found a linear relationship between temperature and arthropod biomass only below temperature thresholds. Higher temperatures were associated with higher peak and seasonal biomass below 106 and 177 cumulative thawing degree‐days, respectively, between June 5 and July 15. Beyond these thresholds, no relationship was observed between temperature and arthropod biomass. Our results suggest that prolonged exposure to elevated temperatures can positively influence prey availability for some arctic birds. This positive effect could, in part, stem from changes in arthropod assemblages and may reduce the risk of trophic mismatch.

The Cerebellar Cognitive Affective/Schmahmann Syndrome Scale in Spinocerebellar Ataxias - Louisa P. Selvadurai; Susan L. Perlman; Tetsuo Ashizawa; George R. Wilmot; Chiadi U. Onyike; Liana S. Rosenthal; Vikram G. Shakkottai; Henry L. Paulson; Sub H. Subramony; Khalaf O. Bushara; Sheng-Han Kuo; Cameron Dietiker; et al. (The Cerebellum, 2024)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Beyond ecology: ecosystem restoration as a process for social-ecological transformation - Anazélia M. Tedesco; Sofía López-Cubillos; Robin Chazdon; Jonathan R. Rhodes; Carla L. Archibald; Katharina-Victoria Pérez-Hämmerle; Pedro H.S. Brancalion; Kerrie A. Wilson; Mariana Oliveira; Diego F. Correa; Liz Ota; Tiffany H. Morrison; et al. (Trends in Ecology & Evolution, 2023)

Research priorities for the sustainability of coral-rich western Pacific seascapes - Graeme S. Cumming; Maja Adamska; Michele L. Barnes; Jon Barnett; David R. Bellwood; Joshua E. Cinner; Philippa J. Cohen; Jennifer M. Donelson; Katharina Fabricius; R. Quentin Grafton; Alana Grech; Georgina G. Gurney; et al. (Regional Environmental Change, 2023)
Nearly a billion people depend on tropical seascapes. The need to ensure sustainable use of these vital areas is recognised, as one of 17 policy commitments made by world leaders, in Sustainable Development Goal (SDG) 14 (‘Life below Water’) of the United Nations. SDG 14 seeks to secure marine sustainability by 2030. In a time of increasing social-ecological unpredictability and risk, scientists and policymakers working towards SDG 14 in the Asia–Pacific region need to know: (1) How are seascapes changing? (2) What can global society do about these changes? and (3) How can science and society together achieve sustainable seascape futures? Through a horizon scan, we identified nine emerging research priorities that clarify potential research contributions to marine sustainability in locations with high coral reef abundance. They include research on seascape geological and biological evolution and adaptation; elucidating drivers and mechanisms of change; understanding how seascape functions and services are produced, and how people depend on them; costs, benefits, and trade-offs to people in changing seascapes; improving seascape technologies and practices; learning to govern and manage seascapes for all; sustainable use, justice, and human well-being; bridging communities and epistemologies for innovative, equitable, and scale-crossing solutions; and informing resilient seascape futures through modelling and synthesis. Researchers can contribute to the sustainability of tropical seascapes by co-developing transdisciplinary understandings of people and ecosystems, emphasising the importance of equity and justice, and improving knowledge of key cross-scale and cross-level processes, feedbacks, and thresholds.

The dispersal ability of the invasive larger grain borer and the cosmopolitan maize weevil after brief exposure to a newer insecticide formulation - Hannah E. Quellhorst; Frank H. Arthur; Kun Yan Zhu; Alex Bruce; William R. Morrison (Journal of Stored Products Research, 2023)

African Aquaculture: Genetic Resource and Traditional Knowledge Access and Benefit Sharing Measures - Fran Humphries; Charles Lawson; John A. H. Benzie; Clare Morrison (Reviews in Fisheries Science & Aquaculture, 2023)

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

The S-Factor, a New Measure of Disease Severity in Spinocerebellar Ataxia: Findings and Implications - Louisa P. Selvadurai; Susan L. Perlman; George R. Wilmot; Sub H. Subramony; Christopher M. Gomez; Tetsuo Ashizawa; Henry L. Paulson; Chiadi U. Onyike; Liana S. Rosenthal; Haris I. Sair; Sheng-Han Kuo; Eva-Maria Ratai; et al. (The Cerebellum, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Climate Change Implications for Tidal Marshes and Food Web Linkages to Estuarine and Coastal Nekton - Denise D. Colombano; Steven Y. Litvin; Shelby L. Ziegler; Scott B. Alford; Ronald Baker; Myriam A. Barbeau; Just Cebrián; Rod M. Connolly; Carolyn A. Currin; Linda A. Deegan; Justin S. Lesser; Charles W. Martin; et al. (Estuaries and Coasts, 2021)
Climate change is altering naturally fluctuating environmental conditions in coastal and estuarine ecosystems across the globe. Departures from long-term averages and ranges of environmental variables are increasingly being observed as directional changes [e.g., rising sea levels, sea surface temperatures (SST)] and less predictable periodic cycles (e.g., Atlantic or Pacific decadal oscillations) and extremes (e.g., coastal flooding, marine heatwaves). Quantifying the short- and long-term impacts of climate change on tidal marsh seascape structure and function for nekton is a critical step toward fisheries conservation and management. The multiple stressor framework provides a promising approach for advancing integrative, cross-disciplinary research on tidal marshes and food web dynamics. It can be used to quantify climate change effects on and interactions between coastal oceans (e.g., SST, ocean currents, waves) and watersheds (e.g., precipitation, river flows), tidal marsh geomorphology (e.g., vegetation structure, elevation capital, sedimentation), and estuarine and coastal nekton (e.g., species distributions, life history adaptations, predator-prey dynamics). However, disentangling the cumulative impacts of multiple interacting stressors on tidal marshes, whether the effects are additive, synergistic, or antagonistic, and the time scales at which they occur, poses a significant research challenge. This perspective highlights the key physical and ecological processes affecting tidal marshes, with an emphasis on the trophic linkages between marsh production and estuarine and coastal nekton, recommended for consideration in future climate change studies. Such studies are urgently needed to understand climate change effects on tidal marshes now and into the future.

Human Actions Alter Tidal Marsh Seascapes and the Provision of Ecosystem Services - Ben L. Gilby; Michael P. Weinstein; Ronald Baker; Just Cebrian; Scott B. Alford; Ariella Chelsky; Denise Colombano; Rod M. Connolly; Carolyn A. Currin; Ilka C. Feller; Alyssa Frank; Janelle A. Goeke; et al. (Estuaries and Coasts, 2021)

Identifying predictors of international fisheries conflict - Jessica Spijkers; Gerald G. Singh; Colette C. C. Wabnitz; Henrik Österblom; Graeme S. Cumming; Tiffany H. Morrison (Fish and Fisheries, 2021)
Marine capture fishery resources are declining, and demand for them is rising. These trends are suspected to incite conflict, but their effects have not been quantitatively examined. We applied a multi‐model ensemble approach to a global database of international fishery conflicts between 1974 and 2016 to test the supply‐induced scarcity hypothesis (diminishing supplies of fishery resources increase fisheries conflict), the demand‐induced scarcity hypothesis (rising demand for fishery resources increases fisheries conflict), and three alternative political and economic hypotheses. While no single indicator was able to fully explain international conflict over fishery resources, we found a positive relationship between increased conflict over fishery resources and higher levels of per capita GDP for the period 1975–1996. For the period 1997–2016, we found evidence supporting the demand‐induced scarcity hypothesis, and the notion that an increase in supply of fishery resources is linked to an increase in conflict occurrence. By identifying significant predictors of international fisheries conflict, our analysis provides useful information for policy approaches for conflict anticipation and management.

Assessing repellency, movement, and mortality of three species of stored product insects after exposure to deltamethrin-incorporated long-lasting polyethylene netting - D. S. Scheff; A. R. Gerken; W. R. Morrison; J. F. Campbell; F. H. Arthur; K. Y. Zhu (Journal of Pest Science, 2021)

Export of photolabile and photoprimable dissolved organic carbon from the Connecticut River - Byungman Yoon; Jacob D. Hosen; Ethan D. Kyzivat; Jennifer H. Fair; Lisa C. Weber; Kelly S. Aho; Rachel Lowenthal; Serena Matt; William V. Sobczak; Jamie B. Shanley; Jon Morrison; James E. Saiers; et al. (Aquatic Sciences, 2021)

Source Switching Maintains Dissolved Organic Matter Chemostasis Across Discharge Levels in a Large Temperate River Network - J. D. Hosen; K. S. Aho; J. H. Fair; E. D. Kyzivat; S. Matt; J. Morrison; A. Stubbins; L. C. Weber; B. Yoon; P. A. Raymond (Ecosystems, 2021)

Biological Control of the Noxious Weed Angled Onion (Allium triquetrum) Thwarted by Endophytic Bacteria in Victoria, Australia - P. Tehranchian; R. J. Adair; T. T. H. Van; P. D. Morrison; H. Williams; A. C. Lawrie (Australasian Plant Pathology, 2020)

Attraction, arrestment, and preference by immature Trogoderma variabile and Trogoderma granarium to food and pheromonal stimuli - William R. Morrison; Robert F. Grosdidier; Frank H. Arthur; Scott W. Myers; Michael J. Domingue (Journal of Pest Science, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Building the Knowledge-to-Action Pipeline in North America: Connecting Ocean Acidification Research and Actionable Decision Support - Jessica N. Cross; Jessie A. Turner; Sarah R. Cooley; Jan A. Newton; Kumiko Azetsu-Scott; R. Christopher Chambers; Darcy Dugan; Kaitlin Goldsmith; Helen Gurney-Smith; Alexandra R. Harper; Elizabeth B. Jewett; Denise Joy; et al. (Frontiers in Marine Science, 2019)

Merlin modulates process outgrowth and synaptogenesis in the cerebellum - A. Toledo; F. Lang; M. Doengi; H. Morrison; V. Stein; S. L. Baader (Brain Structure and Function, 2019)

Enhancement of primary production during drought in a temperate watershed is greater in larger rivers than headwater streams - J. D. Hosen; K. S. Aho; A. P. Appling; E. C. Creech; J. H. Fair; R. O. Hall; E. D. Kyzivat; R. S. Lowenthal; S. Matt; J. Morrison; J. E. Saiers; J. B. Shanley; et al. (Limnology and Oceanography, 2019)
Drought is common in rivers, yet how this disturbance regulates metabolic activity across network scales is largely unknown. Drought often lowers gross primary production (GPP) and ecosystem respiration (ER) in small headwaters but by contrast can enhance GPP and cause algal blooms in downstream estuaries. We estimated ecosystem metabolism across a nested network of 13 reaches from headwaters to the main stem of the Connecticut River from 2015 through 2017, which encompassed a pronounced drought. During drought, GPP and ER increased, but with greater enhancement in larger rivers. Responses of GPP and ER were partially due to warmer temperatures associated with drought, particularly in the larger rivers where temperatures during summer drought were > 10°C higher than typical summer baseflow. The larger rivers also had low canopy cover, which allowed primary producers to take advantage of lower turbidity and fewer cloudy days during drought. We conclude that GPP is enhanced by higher temperature, lower turbidity, and longer water residence times that are all a function of low discharge, but ecosystem response in temperate watersheds to these drivers depends on light availability regulated by riparian canopy cover. In larger rivers, GPP increased more than ER during drought, even leading to temporary autotrophy, an otherwise rare event in the typically light‐limited heterotrophic Connecticut River main stem. With climate change, rivers and streams may become warmer and drought frequency and severity may increase. Such changes may increase autotrophy in rivers with broad implications for carbon cycling and water quality in aquatic ecosystems.

Global environmental governance for conserving migratory shorebirds in the Asia-Pacific - Eduardo Gallo-Cajiao; Tiffany H. Morrison; Pedro Fidelman; Salit Kark; Richard A. Fuller (Regional Environmental Change, 2019)

Differential Proteomics for Distinguishing Ischemic Stroke from Controls: a Pilot Study of the SpecTRA Project - A. M. Penn; V. Saly; A. Trivedi; M. L. Lesperance; K. Votova; A. M. Jackson; N.S. Croteau; R. F. Balshaw; M. B. Bibok; D. S. Smith; K. K. Lam; J. Morrison; et al. (Translational Stroke Research, 2018)

Crowdfunding biodiversity conservation - Eduardo Gallo‐Cajiao; Carla Archibald; Rachel Friedman; Rochelle Steven; Richard A. Fuller; Edward T. Game; Tiffany H. Morrison; Euan G. Ritchie (Conservation Biology, 2018)
Raising funds is critical for conserving biodiversity and hence so is scrutinizing emerging financial mechanisms that may help achieve this goal. Anecdotal evidence indicates crowdfunding is being used to support activities needed for biodiversity conservation, yet its magnitude and allocation remain largely unknown. To help address this knowledge gap, we conducted a global analysis based on conservation‐focused projects extracted from crowdfunding platforms. For each project, we determined the funds raised, date, country of implementation, proponent characteristics, activity type, biodiversity realm, and target taxa. We identified 72 relevant platforms and 577 conservation‐focused projects that raised $4,790,634 since 2009. Although proponents were based in 38 countries, projects were delivered across 80 countries, indicating a potential mechanism of resource mobilization. Proponents were affiliated with nongovernmental organizations (35%) or universities (30%) or were freelancers (26%). Most projects were for research (40%), persuasion (31%), and on‐the‐ground actions (21%). Projects were more focused on species (57.7%) and terrestrial ecosystems (20.3%), and less focused on marine (8.8%) and freshwater ecosystems (3.6%). Projects focused on 208 species, including a disproportionate number of threatened birds and mammals. Crowdfunding for biodiversity conservation is a global phenomenon and there is potential for expansion, despite possible pitfalls (e.g., uncertainty about effectiveness). Opportunities to advance conservation through crowdfunding arise from its capacity to mobilize funds spatially and increase steadily over time, inclusion of overlooked species, adoption by multiple actors, and funding of activities beyond research. Our findings pave the way for further research on key questions, such as campaign success rates, effectiveness of conservation actions, and drivers of crowdfunding adoption. Even though crowdfunding capital raised has been modest relative to other conservation‐finance mechanisms, its contribution goes beyond funding research and providing capital. Embraced with due care, crowdfunding could become an important financial mechanism for biodiversity conservation.

Marine fisheries and future ocean conflict - Jessica Spijkers; Tiffany H Morrison; Robert Blasiak; Graeme S Cumming; Matthew Osborne; James Watson; Henrik Österblom (Fish and Fisheries, 2018)
Conflict over marine fishery resources is a growing security concern. Experts expect that global changes in our climate, food systems and oceans may spark or exacerbate resource conflicts. An initial scan of 803 relevant papers and subsequent intensive review of 31 fisheries conflict studies, focused on subnational and international conflicts, suggests that four substantial scientific gaps need addressing to improve our understanding of the nature and drivers of fisheries conflict. First, fisheries conflict and levels of conflict intensity are not precisely defined. Second, complex adaptive systems thinking is underutilized but has the potential to produce more realistic causal models of fishery conflict. Third, comparative large‐scale data and suitably integrative methodologies are lacking, underscoring the need for a standardized and comparable database of fisheries conflict cases to aid extrapolation beyond single case‐studies. Fourth, there is room for a more widespread application of higher order concepts and associated terminology. Importantly, the four gaps highlight the homogenized nature of current methodological and theoretical approaches to understanding fishery conflict, which potentially presents us with an oversimplified understanding of these conflicts. A more nuanced understanding of the complex and dynamic nature of fishery conflict and its causes is not only scientifically critical, but increasingly relevant for policymakers and practitioners in this turbulent world.

Characterization of isolated liver sinusoidal endothelial cells for liver bioengineering - A. M. Dingle; K. K. Yap; Y-W. Gerrand; C. J. Taylor; E. Keramidaris; Z. Lokmic; A. M. Kong; H. L. Peters; W. A. Morrison; G. M. Mitchell (Angiogenesis, 2018)

Correction to: Genetic and morphological sex identification methods reveal a male-biased sex ratio in the Ivory Gull Pagophila eburnea - Glenn Yannic; Thomas Broquet; Hallvard Strøm; Adrian Aebischer; Christophe Dufresnes; Maria V. Gavrilo; H. Grant Gilchrist; Mark L. Mallory; R. I. Guy Morrison; Brigitte Sabard; Roberto Sermier; Olivier Gilg (Journal of Ornithology, 2018)

Reconstructing governability: How fisheries are made governable - Andrew M Song; Jahn P Johnsen; Tiffany H Morrison (Fish and Fisheries, 2018)
Governability is an important concept in the political and environmental social sciences with increasing application to socio‐ecological systems such as fisheries. Indeed, governability analyses of fisheries and related systems such as marine‐protected areas have generated innovative ways to implement sustainability ideals. Yet, despite progress made, we argue that there remain limitations in current conceptions of governability that hinder further analytical development and use. By drawing on general systems theory—specifically cybernetics, control and feedback—we interrogate the conceptual foundations that underpin two key limitations: the need to incorporate the numerous variables that comprise a complex, holistic system into a singular assessment of governability, and the a priori separation of the governor and the governed that precludes analysis of a self‐governing situation. We argue that by highlighting the reciprocal nature of a governor–governed relationship and the co‐produced understanding of governing capacity and objects, a relational approach to governability is possible. This offers a clearer and more pragmatic understanding of how governors and fishers can make fisheries governable.

The effects of intranasal esketamine (84 mg) and oral mirtazapine (30 mg) on on-road driving performance: a double-blind, placebo-controlled study - Aurora J. A. E. van de Loo; Adriana C. Bervoets; Loes Mooren; Noor H. Bouwmeester; Johan Garssen; Rob Zuiker; Guido van Amerongen; Joop van Gerven; Jaskaran Singh; Peter Van der Ark; Maggie Fedgchin; Randall Morrison; et al. (Psychopharmacology, 2017)

Indigenous arthropod natural enemies of the invasive brown marmorated stink bug in North America and Europe - Paul K. Abram; Kim A. Hoelmer; Angelita Acebes-Doria; Heather Andrews; Elizabeth H. Beers; J. Christopher Bergh; Ric Bessin; David Biddinger; Paul Botch; Matthew L. Buffington; Mary L. Cornelius; Elena Costi; et al. (Journal of Pest Science, 2017)

New Directions for Understanding the Spatial Resilience of Social–Ecological Systems - Graeme S. Cumming; Tiffany H. Morrison; Terence P. Hughes (Ecosystems, 2017)

Mycorrhizal inoculation increases genes associated with nitrification and improved nutrient retention in soil - E. Morrison; L. Lagos; A. Al-Agely; H. Glaab; Winston Johnson; Milko A. Jorquera; A. Ogram (Biology and Fertility of Soils, 2017)

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Institutional capacity for long-term climate change adaptation: evidence from land use planning in Albay, Philippines - Sining C. Cuevas; Ann Peterson; Catherine Robinson; Tiffany H. Morrison (Regional Environmental Change, 2016)

Long‐term epidemiological survey of Kudoa thyrsites (Myxozoa) in Atlantic salmon ( Salmo salar L.) from commercial aquaculture farms - W L Marshall; A Sitjà‐Bobadilla; H M Brown; T MacWilliam; Z Richmond; H Lamson; D B Morrison; L O B Afonso (Journal of Fish Diseases, 2016)
Kudoa thyrsites (Myxozoa) encysts within myocytes of a variety of fishes. While infected fish appear unharmed, parasite‐derived enzymes degrade the flesh post‐mortem. In regions of British Columbia ( BC ), Canada, up to 4–7% of fillets can be affected, thus having economic consequences and impacting the competitiveness of BC 's farms. K. thyrsites was monitored in two farms having high ( HP ) or low ( LP ) historical infection prevalence. At each farm, 30 fish were sampled monthly for blood and muscle during the first year followed by nine samplings during year two. Prevalence and intensity were measured by PCR and histology of muscle samples. In parallel, fillet tests were used to quantify myoliquefaction. Infections were detected by PCR after 355 and 509 degree days at LP and HP farms, respectively. Prevalence reached 100% at the HP farm by 2265 degree days and declined during the second year, whereas it plateaued near 50% at the LP farm. Infection intensities decreased after 1 year at both farms. Blood was PCR ‐positive at both farms between 778 and 1113 degree days and again after 2000 degree days. This is the first monitoring project in a production environment and compares data between farms with different prevalence.

Genetic and morphological sex identification methods reveal a male-biased sex ratio in the Ivory Gull Pagophila eburnea - Glenn Yannic; Thomas Broquet; Hallvard Strøm; Adrian Aebischer; Christophe Dufresnes; Maria V. Gavrilo; H. Grant Gilchrist; Mark L. Mallory; R. I. Guy Morrison; Brigitte Sabard; Roberto Sermier; Olivier Gilg (Journal of Ornithology, 2016)

High connectivity in a long-lived high-Arctic seabird, the ivory gull Pagophila eburnea - Glenn Yannic; Jonathan M. Yearsley; Roberto Sermier; Christophe Dufresnes; Olivier Gilg; Adrian Aebischer; Maria V. Gavrilo; Hallvard Strøm; Mark L. Mallory; R. I. Guy Morrison; H. Grant Gilchrist; Thomas Broquet (Polar Biology, 2016)

Comparison of low-carbon pathways for California - Geoffrey M. Morrison; Sonia Yeh; Anthony R. Eggert; Christopher Yang; James H. Nelson; Jeffery B. Greenblatt; Raphael Isaac; Mark Z. Jacobson; Josiah Johnston; Daniel M. Kammen; Ana Mileva; Jack Moore; et al. (Climatic Change, 2015)

Syndromic surveillance of peste des petits ruminants and other animal diseases in Koinadugu district, Sierra Leone, 2011–2012 - Abu James Sundufu; Rashid Ansumana; Alfred Swarray Bockarie; Umaru Bangura; Joseph Morrison Lamin; Kathryn H. Jacobsen; David Andrew Stenger (Tropical Animal Health and Production, 2015)

Modeling and simulation for medical product development and evaluation: highlights from the FDA-C-Path-ISOP 2013 workshop - Klaus Romero; Vikram Sinha; Sandra Allerheiligen; Meindert Danhof; Jose Pinheiro; Naomi Kruhlak; Yaning Wang; Sue-Jane Wang; John-Michael Sauer; J. F. Marier; Brian Corrigan; James Rogers; et al. (Journal of Pharmacokinetics and Pharmacodynamics, 2014)

Biomass briquettes: a novel incentive for managing papyrus wetlands sustainably? - E. H. J. Morrison; A. Banzaert; C. Upton; N. Pacini; J. Pokorný; D. M. Harper (Wetlands Ecology and Management, 2014)

A Novel Method for Reducing the Effect of Tonic Muscle Activity on the Gamma Band of the Scalp EEG - Judith F. Nottage; Paul D. Morrison; Steve C. R. Williams; Dominic H. ffytche (Brain Topography, 2013)

Population stratification may bias analysis of PGC-1α as a modifier of age at Huntington disease motor onset - Eliana Marisa Ramos; Jeanne C. Latourelle; Ji-Hyun Lee; Tammy Gillis; Jayalakshmi S. Mysore; Ferdinando Squitieri; Alba Di Pardo; Stefano Di Donato; Michael R. Hayden; Patrick J. Morrison; Martha Nance; Christopher A. Ross; et al. (Human Genetics, 2012)

Acinetobacter , Aeromonas and Trichococcus populations dominate the microbial community within urban sewer infrastructure - J. L. VandeWalle; G. W. Goetz; S. M. Huse; H. G. Morrison; M. L. Sogin; R. G. Hoffmann; K. Yan; S. L. McLellan (Environmental Microbiology, 2012)
Summary We evaluated the population structure and temporal dynamics of the dominant community members within sewage influent from two wastewater treatment plants (WWTPs) in Milwaukee, WI. We generated > 1.1 M bacterial pyrotag sequences from the V6 hypervariable region of 16S rRNA genes from 38 influent samples and two samples taken upstream in the sanitary sewer system. Only a small fraction of pyrotags from influent samples (∼ 15%) matched sequences from human faecal samples. The faecal components of the sewage samples included enriched pyrotag populations from Lactococcus and Enterobacteriaceae relative to their fractional representation in human faecal samples. In contrast to the large number of distinct pyrotags that represent faecal bacteria such as Lachnospiraceae and Bacteroides , only one or two unique V6 sequences represented Acinetobacter , Aeromonas and Trichococcus , which collectively account for nearly 35% of the total sewage community. Two dominant Acinetobacter V6 pyrotags (designated Acineto tag 1 and Acineto tag 2) fluctuated inversely with a seasonal pattern over a 3‐year period, suggesting two distinct Acinetobacter populations respond differently to ecological forcings in the system. A single nucleotide change in the V6 pyrotags accounted for the difference in these populations and corresponded to two phylogenetically distinct clades based on full‐length sequences. Analysis of wavelet functions, derived from a mathematical model of temporal fluctuations, demonstrated that other abundant sewer associated populations including Trichococcus and Aeromonas had temporal patterns similar to either Acineto tag 1 or Acineto tag 2. Populations with related temporal fluctuations were found to significantly correlate with the same WWTP variables (5‐day BOD, flow, ammonia, total phosphorous and suspended solids). These findings illustrate that small differences in V6 sequences can represent phylogenetically and ecologically distinct taxa. This work provides insight into microbial community composition and dynamics within the defined environment of urban sewer infrastructure.

Managing the natural capital of papyrus within riparian zones of Lake Victoria, Kenya - E. H. J. Morrison; C. Upton; K. Odhiambo-K’oyooh; D. M. Harper (Hydrobiologia, 2012)

Haplotype structure in Ashkenazi Jewish BRCA1 and BRCA2 mutation carriers - Kate M. Im; Tomas Kirchhoff; Xianshu Wang; Todd Green; Clement Y. Chow; Joseph Vijai; Joshua Korn; Mia M. Gaudet; Zachary Fredericksen; V. Shane Pankratz; Candace Guiducci; Andrew Crenshaw; et al. (Human Genetics, 2011)

Detection of sub-tidal mussel beds on rocky reefs using acoustics - M. A. Morrison; A. G. Jeffs; S. H. Hooker (International Journal of Remote Sensing, 2010)

Feeling good: on the role of C fiber mediated touch in interoception - M. Björnsdotter; I. Morrison; H. Olausson (Experimental Brain Research, 2010)

Paliperidone suppresses the development of the aggressive phenotype in a developmentally sensitive animal model of escalated aggression - Jared J. Schwartzer; Randall L. Morrison; Lesley A. Ricci; Richard H. Melloni (Psychopharmacology, 2009)

Simulation of networks of spiking neurons: A review of tools and strategies - Romain Brette; Michelle Rudolph; Ted Carnevale; Michael Hines; David Beeman; James M. Bower; Markus Diesmann; Abigail Morrison; Philip H. Goodman; Frederick C. Harris; Milind Zirpe; Thomas Natschläger; et al. (Journal of Computational Neuroscience, 2007)

Spatial‐temporal variability in diazotroph assemblages in Chesapeake Bay using an oligonucleotide nifH microarray - Pia H. Moisander; Amanda E. Morrison; Bess B. Ward; Bethany D. Jenkins; Jonathan P. Zehr (Environmental Microbiology, 2007)
Summary The distribution of nitrogen‐fixing microorganisms in the Chesapeake Bay was investigated using fingerprints from a nifH microarray comprised of 706 60‐mer oligonucleotide nifH probes representing cultivated organisms and environmental clones from different nifH clusters. Diverse nifH targets, amplified from samples using degenerate nifH primers, were detected in water column and sediment samples collected in April and October, 2001–2002. Total nifH richness and diversity (Simpson's and Shannon indices) were highest at the most riverine, oligohaline North Bay station. In most samples, the highest diversity was in nifH Cluster 3, which includes many anaerobes, while Cluster 1 (α‐, β‐ γ‐ Proteobacteria, Cyanobacteria) targets had the greatest microarray signal intensities. In a multidimensional scaling analysis, deep water communities from April and October were similar within each of the sampling sites, while the surface communities had more variability. Diazotroph communities in the water column in the North Bay were distinct from the Mid‐ and South Bay communities, and there was a gradual change in sediment diazotroph assemblages from the North to the South Bay. Diazotrophic assemblages from the majority of the water column samples from the Mid‐ and South Bay clustered with the sediment assemblage in Mid‐Bay. Dissolved inorganic nitrogen, salinity, dissolved organic carbon and dissolved organic phosphorus had a significant relationship with the diazotrophic bacterioplankton community. Higher diversity in the freshwater end of the system may reflect variability in disturbance rates and environmental conditions such as forms and concentrations of organic matter, nutrients and oxygen.

Multicenter retrospective development and validation of a clinical prediction rule for nosocomial invasive candidiasis in the intensive care setting - L. Ostrosky-Zeichner; C. Sable; J. Sobel; B. D. Alexander; G. Donowitz; V. Kan; C. A. Kauffman; D. Kett; R. A. Larsen; V. Morrison; M. Nucci; P. G. Pappas; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2007)

The Multifaceted Nature of Biodiversity Conservation: Reply to Leroux and Schmiegelow - JOHN F. LAMOREUX; JOHN C. MORRISON; TAYLOR H. RICKETTS; DAVID M. OLSON; ERIC DINERSTEIN; MEGHAN W. McKNIGHT; HERMAN H. SHUGART (Conservation Biology, 2007)

An Assessment of Turbulence Profiles in Rural and Urban Environments Using Local Measurements and Numerical Weather Prediction Results - N. L. Morrison; H. N. Webster (Boundary-Layer Meteorology, 2005)

Beyond Noah: Saving Species Is Not Enough - JONATHAN V. HIGGINS; TAYLOR H. RICKETTS; JEFFREY D. PARRISH; ERIC DINERSTEIN; GEORGE POWELL; SUZANNE PALMINTERI; JONATHAN M. HOEKSTRA; JOHN MORRISON; ADAM TOMASEK; JONATHAN ADAMS (Conservation Biology, 2004)

Short-Term Toxicity and Binding of Platinum to Freshwater Periphyton Communities - S. Rauch; M. Paulsson; M. Wilewska; H. Blanck; G. M. Morrison (Archives of Environmental Contamination and Toxicology, 2004)

Comparative Tissue Distribution of Metals in Birds in Sweden Using ICP-MS and Laser Ablation ICP-MS - Kristine H. Ek; Gregory M. Morrison; Peter Lindberg; Sbastien Rauch (Archives of Environmental Contamination and Toxicology, 2004)

Microtubule assembly in cultured myoblasts and myotubes following nocodazole induced microtubule depolymerisation - H. Musa; C. Orton; E.E. Morrison; M. Peckham (Journal of Muscle Research and Cell Motility, 2003)

Identification and characterization of a novel murine beta-defensin-related gene - Gillian M. Morrison; Mark Rolfe; Fiona M. Kilanowski; Sally H. Cross; Julia R. Dorin (Mammalian Genome, 2002)

Platinum Group Elements in the Feathers of Raptors and Their Prey - K. H. Jensen; S. Rauch; G. M. Morrison; P. Lindberg (Archives of Environmental Contamination and Toxicology, 2002)

Cytotoxicity of trichothecenes and fusarochromanone produced byFusarium equiseti strains isolated from Norwegian cereals - Ellen Morrison; Thomas Rundberget; Barbara Kosiak; Are H. Aastveit; Aksel Bernhoft (Mycopathologia, 2002)

Leftward shift in the acquisition of cocaine self-administration in isolation-reared rats: relationship to extracellular levels of dopamine, serotonin and glutamate in the nucleus accumbens and amygdala-striatal FOS expression - Simon R. Howes; Jeffrey W. Dalley; Caroline H. Morrison; Trevor W. Robbins; Barry J. Everitt (Psychopharmacology, 2000)

Effect of ethanol on myocardial infarct size in a canine model of coronary artery occlusion-reperfusion - Masao Itoya; Jeffrey D. Morrison; H. Fred Downey (Molecular and Cellular Biochemistry, 1998)

The identification of novel sequences expressed in the mouse notochord - J. C. Sowden; K. Morrison; W. Putt; R. Beddington; Y. H. Edwards (Mammalian Genome, 1997)

Flavor and chemical evaluation of partially hydrogenated sunflower oil as a potato chip frying oil - J. A. Robertson; W. H. Morrison; D. Burdick; Roy Shaw (American Journal of Potato Research, 1972)

The changing role of soil pests attacking potato tubers - H. E. Morrison; L. G. Gentner; R. F. Koontz; R. W. Every (American Journal of Potato Research, 1967)

Conversionin vitro of a human pleuropneumonia-like organism to aCorynebacterium - Thomas H. Morrison; Ruth G. Wittler; John E. Faber (Antonie van Leeuwenhoek, 1961)